2017
DOI: 10.1038/s41598-017-06874-w
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1B mutations associated with metabolic syndrome impair the chaperone-dependent maturation of the kinase domain

Abstract: Two missense mutations of the DYRK1B gene have recently been found to co-segregate with a rare autosomal-dominant form of metabolic syndrome. This gene encodes a member of the DYRK family of protein kinases, which depend on tyrosine autophosphorylation to acquire the catalytically active conformation. The mutations (H90P and R102C) affect a structural element named DYRK homology (DH) box and did not directly interfere with the conformation of the catalytic domain in a structural model of DYRK1B. Cellular assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 43 publications
2
45
0
Order By: Relevance
“…Wild-type (wt) and mutant GFP-DYRK1A fusion proteins were immunoprecipitated with a GFP antibody from cell extracts of transiently transfected HEK293 cells and subjected to immunoblot analysis. Tyrosine phosphorylation of the activation loop (Y321) was analyzed using an antibody against the activation loop tyrosine in HIPK2 that cross-reacts with the corresponding residue in DYRK1A ( Abu Jhaisha et al, 2017 ). Relative tyrosine phosphorylation was calculated ratio of the pY321 signal relative to total amounts DYRK1A constructs as detected with a DYRK1A specific antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wild-type (wt) and mutant GFP-DYRK1A fusion proteins were immunoprecipitated with a GFP antibody from cell extracts of transiently transfected HEK293 cells and subjected to immunoblot analysis. Tyrosine phosphorylation of the activation loop (Y321) was analyzed using an antibody against the activation loop tyrosine in HIPK2 that cross-reacts with the corresponding residue in DYRK1A ( Abu Jhaisha et al, 2017 ). Relative tyrosine phosphorylation was calculated ratio of the pY321 signal relative to total amounts DYRK1A constructs as detected with a DYRK1A specific antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Rabbit polyclonal antibody against phospho-HIPK2 (pTyr361) was purchased from Thermo Fisher Scientific (#PA5-13045; RRID:AB_10987115) and used at 1:1000 dilution for western blot detection. We have previously shown that this antibody is suitable for detection of pY321 in DYRK1A, due to the sequence similarity of the activation loop in HIPK2 and DYRK1A ( Abu Jhaisha et al, 2017 ). Goat polyclonal antibody against GFP was from Rockland Immunochemicals (Limerick, PA, USA; #600-401-215; RRID:AB_828167) and used at 1:1000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined phospho-Dyrk1b (p-Y273) levels in C2C12 cells after treatment with cyclopamine. The antibody against p-HIPK2 cross-reacts with the phospho-Y273 residue of the Dyrk1b protein and was previously used to assess Dyrk1b activation (45). WB analysis in cyclopamine treated C2C12 cells revealed higher Dyrk1b auto-phosphorylation upon Shh inhibition compared to untreated cells ( Fig.…”
Section: Dyrk1b Is Activated By Shh Inhibition and Promotes Myotube Fmentioning
confidence: 99%
“…This holds particularly true for DYRK1B carrying mutations which were identified in families suffering from an autosomal-dominant form of metabolic syndrome [ 35 ], a disease with prominent adipocyte involvement. The mutations found result in misfolding of the DYRK1B protein and in intracellular aggregation [ 124 ]. It remains to be clarified how these mutations affect the functional integration of DYRK1B into other signaling pathways, but it is intriguing to note that mutant DYRK1B expression reduced GLI2 levels in cultured adipocytes [ 35 ].…”
Section: Class I Dyrks: Dyrk1a and Dyrk1bmentioning
confidence: 99%